KONSTITUEN PENGUNGKAP NEGASI DALAM BAHASA MAKASSAR DIALEK LAKIUNG DAN TURATEA (Constituent of Negation Expression in Makassarese Language Dialect of Laking and Turatea) - Ramlah Mappau (SAWERIGADING, 2017)
The usage of Makassarese language could be the research object on account of having many dialect variations and one of Austronesian language existing until today; its speakers are also still found in the capital Province of South Sulawesi. The preservation efforts are necessary to do either on script or anthropology aspects.Language structure has its own identity in which each part reflects its identity and relates to. Therefore, the study of negation as one of the parts of language structure is interesting to do. It belongs to descriptive in order to describe negation constituent in Lakiung and Turatea dialect of Makassarese language. For getting factual, informative, and accurate explanation, field and library researches are done. Data collection is done by observation with listening and noting technique, whether on written or oral data. Data analysis is donethrough three levels, providing, analyzing, and displaying data analyzed. In selecting data, identification technique is used to describe negation form and its variations and its usage in the sentences. Negation forms found in Lakiung and Turatea dialects of Makassarese language based on analysis is bound morpheme taKand its alomorf and free morpheme such as tena, tea in Lakiung dialects tania (tangia) tanre, tea followed by pronoun in Turatea dialectAbstrakPenggunaan bahasa Makassar dapat dijadikan sebagai objekk kajian karena bahasa Makassar yang beragam dialek adalah salah satu bahasa Austronesia yang masih bertahan hingga kini, penggunaannya pun masih ditemukan di ibukota provinsi. Upaya pelestariannya terus diupayakan baik pada aspek aksara hingga pada aspek antropolisnya. Bentuk negasi adalah salah satu aspek dalam bahasa. Bentuk negasi  dalam bahasa Makassar berdasarkan analisis data ditemukan bentuk negasi dalam dialek Lakiung dan Turatea yang berupa bentuk terikat, seperti taK- dan alomorfnya. Selain itu, ditemukan pula bentuk bebas, seperti tena, tea dalam dialek Lakiung tania (tangia) tanre, tea yang diikuti pronomina dalam dialek Turatea. Analisis data dalam penelitian ini dilakukan dengan tiga tahap, yaitu penyediaan data, analisis data, dan penyajian hasil analisis. Setiap tahapan itu mempunyai metode yang dijabarkan dalam teknik-teknik sesuai dengan hakikat objek penelitian dan sifat penelitian ini. Data yang diperoleh dari sumber lisan dan tertulis dilakukan melalui metode observasi dengan teknik simak dan catat. Dalam pemilahan data digunakan teknik identifikasi, yaitu dengan memperhatikan distribusi, fungsi, dan makna konstituen negatif dalam setiap tataran gramatikal. Teknik ini digunakan dengan tujuan mendeskripsikan bentuk negasi dan variasi-variasi serta pemakaiannya di dalam kalimat.  Abstract            The using of Makassarese language can be made into research object because it has may dialect variations, and one of the variation is Austronesian that is still survive until now, and its using is still can be found in capital of the province. The revitalization efforts are still sought on script aspects and antropolis aspects. Negation form is one of the language aspects. Makassarese negation form is based on data analysis found that negation form in Lakiung dan Turatea dialect are bound form, such as taK- dan its alomorf. Besides, the writer found free form, such as tena, tea in Lakiung dialect tania (tangia), tanre, tea that followed by pronomina in Turatea dialect. Data analysis ini this research was done by  three steps, step one is provision of data, step two is analysis of data, and step three is presentation of the analysis results. Every steps has desribed methods in techniques based on the research object dan the nature of the research. The data taken from oral and written sources through observation methods with listen and note technique. In choosing data, the writer uses identification technique with pay attention to distribution, function, and negative constituent meaning in every gramatical order. This technique is used to desribe negation form and it variations, and its usage in sentences.Key Words: dialect, Makassarese, dan negation